Racial and ethnic differences in epigenetic aging: The National Health and Nutrition Examination Survey, 1999-2002. - Belinda L Needham; Nicole Gladish; Hanyang Shen; Yongmei Liu; Jennifer A Smith; Bhramar Mukherjee; Xiang Zhou; David H Rehkopf (PLoS ONE, 2025)
Background Accelerated biological aging due to differences in socially patterned exposures has been proposed as a mechanism underlying racial and ethnic disparities in morbidity and mortality. Research exploring this hypothesis has been limited by a lack of consensus regarding the measurement of biological aging. Objective The goal of this study is to examine self-reported race and ethnicity as a predictor of 13 measures of epigenetic aging. Methods Data are from the National Health and Nutrition Examination Survey (1999-2002), a nationally representative study of US residents aged two months and older. The analytic sample includes 2,402 adults aged 50-84 with epigenetic data. The exposure is self-reported race and ethnicity, and the outcomes are 13 measures of epigenetic aging trained on different aging phenotypes. Results In linear regression models controlling for age, age-squared, gender, and nativity, White respondents had higher epigenetic aging than Black respondents (the reference group) for six out of seven measures trained on chronological age (Hannum: b = 1.98, 95% CI = 1.43, 2.54; Horvath: b = 0.75, 95% CI = 0.09, 1.40; Weidner: b = 1.15, 95% CI = 0.30, 2.01; Vidal-Bralo: b = 2.30, 95% CI = 1.76, 2.84; SkinBlood: b = 0.85, 95% CI = 0.28, 1.43; Zhang: b = 0.58, 95% CI = 0.40, 0.76) and for one measure trained on telomere length (b = -0.17, 95% CI = -0.20, -0.14). In contrast, White respondents had lower epigenetic aging than Black respondents for three out of four measures trained on physiological age (GrimAge: b = -1.33, 95% CI = -2.01, -0.64; DunedinPoAm: b = -0.03, 95% CI = -0.04, -0.01; GrimAge2: b = -1.97, 95% CI = -2.74, -1.20) and for one measure trained on stem cell divisions (b = -0.01, 95% CI = -0.01, -0.01). Fewer differences in epigenetic aging were observed when comparing Mexican American, other Hispanic, and another race or ethnicity respondents to Black respondents. Conclusions White respondents had higher epigenetic aging than Black respondents for measures trained on chronological age, whereas the opposite was true for measures trained on physiological age. More work is needed to validate measures of epigenetic aging in non-White populations and to determine whether these measures are associated with health-related outcomes similarly across racial and ethnic groups.